Stress analysis using brittle lacquer techniques and strain gauging - 275747 Khairuddin Mat Arif (Kuala Lumpur : UTM, 1983)
Thesis (Bachelor in Mechanical Engineering) - Universiti Teknologi Malaysia, 1983